PENGARUH MODEL PEMBELAJARAN QUANTUM TEACHING TERHADAP MINAT BELAJAR IPA DI SEKOLAH DASAR - Irviana, Ira (ALENA : Journal of Elementary Education, 2023)
This research aims to; 1) find out the description of the use of the Quantum Teaching model on interest in learning science in class IV students of SD Negeri Daya 1 Makassar, 2) find out the use of the Quantum Teaching learning model can affect interest in learning science in class IV students of SD Negeri Daya 1 Makassar, 3) To knowing the role of the Quantum Teaching learning model can influence the interest in learning science in grade IV SD Negeri Daya 1 Makassar. This type of research is quasi-experimental quantitative. The population and sample used in this study used total sampling so that 30 students were obtained from the total number of students. The instrument used was an interest learning questionnaire to find out the results of the scores in the form of observation sheets and multiple choice questions in pretest and posttest, data collection techniques using questionnaires and observations for students and teachers. The results of the study show that there is an influence of the quantum teaching-learning model on interest in learning science. There is an influence of the quantum teaching-learning model on interest in learning science in fourth-grade students of SD Negeri Daya 1 Makassar, as evidenced by the hypothesis test, and it can be seen that the significant value of the interest in learning science is 0.003 <0.05. Then there is the influence of the quantum teaching-learning model on interest in learning science. Also seen from the t value, count 3.229 and table 0.444, so that it can be seen that the count value is 3.229 > 0.444, there is a significant influence of the quantum teaching-learning model on interest in learning science.